2018
DOI: 10.1186/s12962-018-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Brief interventions to address substance use among patients presenting to emergency departments in resource poor settings: a cost-effectiveness analysis

Abstract: BackgroundThere are limited data describing the cost-effectiveness of brief interventions for substance use in resource-poor settings. Using a patient and provider perspective, this study investigates the cost-effectiveness of a brief motivational interviewing (MI) intervention versus a combined intervention of MI and problem solving therapy (MI-PST) for reducing substance use among patients presenting to emergency departments, in comparison to a control group.MethodsEffectiveness data were extracted from Proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The terms community health workers and facility-based counsellors are often used to describe a certain cadre of non-professional healthcare worker who does not have any health qualification but is trained to deliver a specific low-intensity service. This cost-saving approach is particularly attractive in LMIC settings, such as South Africa, for tackling widespread public health issues [ 21 ]. While SBIRT programmes using a task-sharing approach employing nurses or social workers have been found to be effective and acceptable to patients in healthcare settings, few studies have explored patient experiences and the acceptability of community health worker or facility-based counsellor-delivered SBIRT [ 22 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The terms community health workers and facility-based counsellors are often used to describe a certain cadre of non-professional healthcare worker who does not have any health qualification but is trained to deliver a specific low-intensity service. This cost-saving approach is particularly attractive in LMIC settings, such as South Africa, for tackling widespread public health issues [ 21 ]. While SBIRT programmes using a task-sharing approach employing nurses or social workers have been found to be effective and acceptable to patients in healthcare settings, few studies have explored patient experiences and the acceptability of community health worker or facility-based counsellor-delivered SBIRT [ 22 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This observed burden in the injured population suggests that the EC venue may be an impactful environment to access and provide care for substance use disorders in Kenya and other similar settings. Furthermore as the EC treatment period has been documented as a setting in which health promotion and readiness to change is present, interventions for substance use may be both feasible and efficacious [33] , [34] , [35] . However, there is an urgent need for research into how to best develop and implement substance use assistance interventions in the EC setting in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of treatment over the intervention period ranged from weekly (Chang et al, 2018;Hamdani et al, 2020;Lund et al, 2020) to fortnightly (Patel et al, 2003;Nadkarni et al, 2017;Adewuya et al, 2019;Gureje et al, 2019a). Duration of treatment ranged from a minimum of 4 weeks (brief treatments for AUDs) (Nadkarni et al, 2016;Dwommoh et al, 2018) up to a maximum of 12 months (perinatal depression) (Fuhr et al, 2019). Three studies provided booster sessions, two as part of the treatment programme (Sava et al, 2009;Adewuya et al, 2019) and the other where the booster sessions were modelled in a separate study (Siskind et al, 2008).…”
Section: Treatment Type Intensity and Durationmentioning
confidence: 99%
“…A provider perspective was exclusively applied in 3 of the 18 studies that stated the perspective (Araya et al, 2006;Hamdani et al, 2020;Nakimuli-Mpungu et al, 2020). Nine of the 18 studies that stated the perspective reported both provider and societal perspectives (Nadkarni et al, 2016;Patel et al, 2017;Weobong et al, 2017;Dwommoh et al, 2018;Fuhr et al, 2019;Sikander et al, 2019;Sun et al, 2021). Six studies adopted a societal perspective exclusively (6/18) (Moraes et al, 2010;McBain et al, 2016;Gal á rraga et al, 2017;Chang et al, 2018;Lund et al, 2020;Blackburn et al, 2021) including the two studies reporting CBA results.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation